Interactional features of some Spanish sequential markers: a conversation-analytic study of linguistic particles - Vázquez Carranza, Ariel (Círculo de Lingüística Aplicada a la Comunicación, 2018)
With naturally occurring interactional data and the methodology of Conversation Analysis, the present paper reports on the interactional features of six Spanish linguistic particles (no, pues, oye, o sea, ah y ay) or sequential markers as they are defined here. Sequential markers have a deictic and initial function, that is, they refer to previous talk or they initiate a new interactional activity. Sequential markers are turn constructional units in their own right since they may project a transition relevance place. Similarly, sequential markers constitute social actions in interaction by themselves. The conversational study of these linguistic elements shows cultural and linguistic aspects of the speakers. This type of linguistic particles may be part of the universal “engine” of human interaction.